2008
DOI: 10.1369/jhc.2008.952499
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of Aquaporin 1, 5, and 9 in the Female Pig Reproductive System

Abstract: (SN) S U M M A R Y Thirteen mammalian aquaporin (AQP) isoforms have been identified, and they have a unique tissue-specific pattern of expression. AQPs have been documented in the reproductive system of both male and female humans, rats, and mice. However, tissue expression and cellular and subcellular localization of AQPs are unknown in the female reproductive system of pigs. In this study, AQP1 immunoreactivity was detected in the capillary endothelium of the ovary. Distinct immunolabeling of capillary en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
87
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(92 citation statements)
references
References 32 publications
5
87
0
Order By: Relevance
“…Our previous study (Skowronski et al 2009) showed the same pattern of labeling of the above-mentioned AQPs in the pig oviduct on days 17 to 19 of the estrous cycle. Branes et al (2005) demonstrated that the oviduct of cycling rats expresses AQP5, 8, and 9 in epithelial cells.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Our previous study (Skowronski et al 2009) showed the same pattern of labeling of the above-mentioned AQPs in the pig oviduct on days 17 to 19 of the estrous cycle. Branes et al (2005) demonstrated that the oviduct of cycling rats expresses AQP5, 8, and 9 in epithelial cells.…”
Section: Discussionsupporting
confidence: 56%
“…In our previous study, immunohistochemistry and Western blot analyses using antibodies against nine AQPs (AQP1,2,3,4,5,7,8,9, and 11) were performed to examine which of these water channel proteins are expressed in the pig oviduct (on days 17-19 of the estrous cycle). The analysis confirmed the expression of AQP1, 5, and 9 (Skowronski et al 2009). …”
supporting
confidence: 61%
“…Subsequent studies have identified more than 10 different types of AQPs in mammals, found in several organs of different species, such as human kidney (Deen et al, 1994), rat epithelial tissue (Lindsay and Murphy, 2007), human blood vessels (Agre and Kozono, 2003), reproductive system of rodents (McConnell et al, 2002), dogs (Domeniconi et al, 2007), and pigs (Skowronski et al, 2009). The studies with AQP1 demonstrated that these proteins are small and integral membrane protein types, crossing the membrane from side to side, and containing two semipores that together form a water channel (Verkman and Mitra, 2000), assisting the transport of solutes (Thoroddsen et al, 2011).…”
Section: Aquaporinsmentioning
confidence: 99%
“…In these original reports, AQP9 mRNA expression was found in a few tissues, most notably liver and leukocytes in humans (Ishibashi et al 1998;Tsukaguchi et al 1999), as well as liver and immature sperm in mice (Tsukaguchi et al 1998). Since then, AQP9 immunoreactivity has been found in many tissues, including rat and human epididymis (Elkjaer et al 2000;Pastor-Soler et al 2001), various cell types of rodent and primate brain (Elkjaer et al 2000;Badaut et al 2001;Badaut et al 2004;Amiry-Moghaddam et al 2005;Arcienega et al 2010), mouse spinal cord (Oshio et al 2004), human chorioamnion and placenta (Damiano et al 2001;Wang et al 2004), mouse and human inner ear (Huang et al 2002;Degerman et al 2011), mouse and human small intestine (Okada et al 2003), rat and human prostate (Wang et al 2008;Hwang et al 2012), human skeletal muscle (Inoue et al 2009), urothelium (Rubenwolf et al 2009), rat and porcine oviduct (Skowronski et al 2009), human adipose tissue (Rodriguez et al 2011), human retina (Tran et al 2013;Yang et al 2013), and mouse and human skin (Sugiyama et al 2014). …”
Section: Introductionmentioning
confidence: 99%